“Lovers are poets”: a reflection on love and poetry - Ramli, Shahriza Ilyana; Saad, Sharina; Yusoff, Zaidi (Universiti Teknologi MARA, Kedah, 2025)
Do you agree with the quote that says, 'Lovers are poets' duo'? Love, oh love! When you're in love, your words become a bit poetic. Your feelings become a little more romantic, and your words take on a rhythm while your thoughts drum into a rhyme. Unintentionally, you turn into a poet, and your words become poetry. The moment you can sit down with a pen in your hand is a moment of joy. This is when you will pen down all your expressions, which are an expression of your romantic thoughts. This is when you breathe metaphors, and your whole universe is onomatopoeia. You make your poems dance, sigh, bow, sing, laugh, and cry." Perhaps it was just an exaggeration, but there might be some truth in it. When you're in love, you become a poet. A poem requires both the writer and the reader to slow down and breathe in the emotions. Therefore, the discussion will focus on why poetry is the preferred language for expressing love and how a poem's conceits help to tame this sometimes uncontrollable emotion.